The role of accounting accruals for the prediction of future cash flows: Evidence from Spain - Laura Arnedo; Fermín Lizarraga; Santiago Sánchez (SERIEs - Journal of the Spanish Economic Association, 2012)
The aim of this study is to determine whether accruals have information value beyond that provided by isolated current cash flows for the prediction of future cash flows. Using a sample of 4,397 Spanish companies (mostly privately held), we estimate in-sample regressions of future cash flows on isolated current cash flows and on accrual-based earnings. We then find that the out-of-sample prediction errors provided by the accrual-based earnings model are significantly lower than those obtained with the cash flows model. We also regress the decrease in prediction errors brought about by the addition of accruals on a set of firm-specific circumstances where accounting manipulation is expected. In all cases the decrease in prediction errors is significantly affected in the hypothesized direction.
Keywords: M41; 330; cash flows; accruals; prediction; Jahresabschluss; Cash Flow; Prognoseverfahren; Privatwirtschaft; Spanien